Evaluation of the serum-free light chain test in untreated patients with AL amyloidosis - Bochtler, Tilmann; Heiß, Christiane; Benner, Axel; Cremer, Friedrich Walter; Volkmann, Martin; Ludwig, Jochen; Dengler, Jolanta; Ho, Anthony Dick; Goldschmidt, Hartmut; Schönland, Stefan (Haematologica, the hematology journal, 2008)
We evaluated the Serum Free Light Chain (FLC) test in a series of 133 untreated patients with systemic AL amyloidosis. The FLC test detected the monoclonal gammopathy in 87% compared with 92% for immunofixation of serum and urine in combination. However, both tests proved complementary. The FLC test was also a valuable tool in patients with advanced renal failure in spite of uninvolved light chain retention. Higher FLC levels were associated with higher bone marrow plasmocytosis, poorer Karnofsky index and heart involvement, and therefore reflected disease severity.
Gesehen am 22.01.2022